Study of anisotropy of extremely high energy cosmic rays (International Journal of Mathematics and Physics, 2016)
The article shows investigations of anisotropy of high energy cosmic rays.We calculated the number of cosmic rays (events) of extremely high energies with different threshold energy, the direction of arrival of which lies on the angular distances from the active galactic nuclei, not large than given. Similar calculations were also carried with maximum of one hundred numerical experiments of concentrating around active galactic nuclei isotropic distribution of particles. For interval to ~30 in all cases, except for a local minimum at ~20 for distance